Effects of peer-led education on knowledge, attitudes, practices of stoma care, and quality of life in bladder cancer patients after permanent ostomy - Ding, Juan-Ying; Pan, Ting-Ting; Lu, Xu-Jing; You, Xiao-Ming; Qi, Jia-Xian (Frontiers in Medicine, 2024)
Objective To investigate the effects of peer-led intervention on knowledge, attitudes, and practices (KAP) of stoma care, as well as quality of life in bladder cancer patients post-permanent ostomy. Methods A series of 340 eligible bladder cancer patients who underwent permanent ostomy from January 2019 to December 2022 were enrolled in this study. These participants were randomly assigned to the intervention group (peer-led intervention) and the control group (routine health intervention) using random number table, with 170 cases in each group. A 30-item questionnaire was used to evaluate knowledge, healthy attitudes, and healthy practices (KAP) of disease; the WHO Quality of Life-100 (WHOQOL-100) was utilized to assess the quality of life among patients; and the incidence of complications in two groups were also recorded during six-month intervention. For the comparison of continuous variables within and between groups, paired sample and independent t-test were applied. The categorical variables analyzed using x2 test or rank-sum test. Results After six-month intervention, 144 participants in the intervention group and 151 participants in the control group were finally retained in this study. The scores of the 20 items in KAP (including basic knowledge of disease, basic knowledge of ostomy, observation of stoma, etc.) in the intervention group were significantly higher than those in the control group (all p < 0.05); the scores of 12 items in WHOQOL-100 (including the positive feelings, thinking, learning, memory and concentration, etc.) in the intervention group were markedly higher than those in the control group, while negative feelings and dependence on medical support in the intervention group were significantly lower than those in the control group (all p < 0.05); the total rate of complications in the intervention group was significantly lower than that in the control group (18.31% vs. 31.13%, p < 0.05). Conclusion The peer-led intervention has a positive effect on improving patients’ KAP of stoma care and quality of life and reducing the rate of complications, which enables it to be a favorable intervention approach for patients with permanent ostomy.